2018
DOI: 10.3389/fpsyg.2018.01289
|View full text |Cite
|
Sign up to set email alerts
|

Different Shades—Different Effects? Consequences of Different Types of Destructive Leadership

Abstract: Destructive leadership comes in many shapes and forms. From reviewing the literature, we conclude that three major forms of destructive leader behaviors are described: (1) follower-directed destructive behaviors, i.e., genuine abusive forms of destructive leadership, (2) organization-directed behaviors, i.e., behaviors such as stealing from the organization or embezzlement, and (3) self-interested destructive leader behavior, i.e., leader who exploit others to reach their goals. One can easily imagine that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
125
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 61 publications
5
125
1
2
Order By: Relevance
“…The research on exploitative leadership is currently in the starting stage. Until now, only two studies have directly investigated exploitative leadership (for reference, see Schmid, Pircher Verdorfer, & Peus, 2018; Schmid et al., 2019). Both studies were conducted in Germany.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The research on exploitative leadership is currently in the starting stage. Until now, only two studies have directly investigated exploitative leadership (for reference, see Schmid, Pircher Verdorfer, & Peus, 2018; Schmid et al., 2019). Both studies were conducted in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies were conducted in Germany. The first study tested the impact of exploitative leadership on employee emotions and turnover intention, whereas the second study revealed its two adverse outcomes, namely workplace deviance and job burnout (Schmid et al, 2018; Schmid et al., 2019). Apart from its negative consequences for employees, there is very little known about this leadership style.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A careful analysis of the existing literature reveals that with only a few exceptions ( Pearce and Sims, 2002 ; Bligh et al, 2007 ; Spain et al, 2016 ; Skogstad et al, 2017 ), leadership research is saturated with studies highlighting the positive side of a leader. However, with an increase in awareness regarding the costs associated with dark leadership style and its negative and dysfunctional consequences, researchers are realizing that there is a strong need to examine dark leadership styles in different contexts ( Karakitapoğlu-Aygün and Gumusluoglu, 2013 ; Arnulf et al, 2016 ; Schmid et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%